Breast cancer presentation and therapy in migrant versus native German patients: contrasting and convergent data of a retrospective monocentric study - Au, Alexandra von; Weiler, Ulrike Karolin; Stefanovic, Stefan; Wallwiener, Markus; Heil, Jörg; Golatta, Michael; Rom, Joachim; Sohn, Christof; Schneeweiss, Andreas; Schütz, Florian; Domschke, Christoph (Archives of gynecology and obstetrics, 2015)
PurposeThe aim of this study was to identify differences between breast cancer patients with and without migrant background in Germany, especially differences concerning patient characteristics, tumor biology, diagnostics, therapy, and oncological outcome.Patients and methodsIn 99 breast cancer patients (composed of 50 native, randomly selected Germans and 49 consecutively selected immigrants of Anatolian origin) who were operated due to breast cancer at the Heidelberg University Hospital between the years 2009-2012, relevant information was retrospectively reviewed.ResultsPatients with migrant background were significantly younger at the time of receiving the diagnosis of breast cancer than native German patients with an average age difference of nine years (p < 0.001). Moreover, immigrants needed a second operation for re-excision more frequently than native Germans (45 vs. 20 %, p = 0.01). The medication used for hormone therapy was significantly different between the two cohorts (p = 0.049). Although statistically not significant, a tendency towards difference was observed in six characteristics examined: Premenopausal status, estrogen receptor-positive tumors, multifocal or bilateral tumors, BRCA-1 mutations, and an accompanying carcinoma in situ were more common in patients with migrant background. On the other hand, correspondence was found between both patient groups relating to tumor staging, grading and metastasis as well as surgical, drug, and radiologic therapies employed. Oncologic outcome data were not different either.ConclusionA difference in age between breast cancer patients of diverse ethnic groups has already been described previously. The difference in the frequency of surgical re-excision might be explained by several factors like a young age at first diagnosis, premenopausal status, multifocal tumors and an accompanying carcinoma in situ which were more common in the migrant patients of this study and are known to increase the risk of re-excision. The medication used for hormonal therapy was also different between migrants and native Germans, which might be interpreted by the difference in patients’ age and menopausal status. Of note, however, in the present study, the overall breast cancer outcome did not show any substantial disparity between the different ethnic patient groups investigated.